Students for practical learning readiness in vocational education: A post-pandemic survey - Nur Kholifah; Muhammad Nurtanto; Farid Mutohhari; Urip Wahyuningsih; Sri Listiani (Journal of Pedagogical Research, 2024)
The post-pandemic era of COVID-19 still leaves crucial problems for vocational education (VE). Practical learning readiness (PLR), which includes dimensions of readiness to support knowledge, and physical and psychological conditions of students, is a fundamental problem that must be resolved through systematic mapping. Therefore, this encourages us to measure the level of readiness from these three dimensions. Apart from that, we also examine the differences in dimensions and indicators and test the determination in constructing PLR to determine problem-solving systematically. The survey was conducted on 386 vocational students, but the final number was 339, considering that 47 of them did not have good rational data level criteria. The results of the descriptive analysis show that psychological conditions and supporting knowledge are at a low level, while physical conditions are at a high level. The results of the comparison test show that the three are generally not significantly different, although there are notes on several indicators. Even though all dimensions contribute significantly to building PLR, psychological conditions make the highest contribution. This shows that a low psychological condition is the first step in suffering from VE. Furthermore, several notes regarding the reduction in knowledge-supporting practices are also the second effort that VE must make to increase PLR among its students.